Estudo de viabilidade da redução de custos logísticos pela introdução de secadores solares na secagem de lodo de esgoto sanitário doméstico - Cabezas, Mario Eduardo (2021)
The main objective of this work was to present the main competitive factors that affect the introduction of the equipment, a solar sanitary sludge dryer, downstream of the current domestic sewage treatment process that takes place in an ETE – Sewage Treatment Station – in Brazil. This study addressed, from the point of view of the ETE, the factors that threaten and those that favor the verticalization and competitiveness of the sanitary treatment chain. For this purpose, a single case study was used, using a quantitative and exploratory approach, with data collection carried out at an ETE in the state of São Paulo. From this work, it can be concluded that the use of the solar dryer in solving sludge problems generated by ETEs stands out in meeting important economic and environmental goals. The result of the investigation of the case study demonstrated that the verticalization of the sanitary process by introducing solar drying is an important process for the management of sewage sludge, as it reduces the mass and volume of the sludge and, consequently, reduces the cost of handling, transporting and disposing of this sludge